IGF2R Genetic Variants, Circulating IGF2 Concentrations and Colon Cancer Risk in African Americans and Whites - Cathrine Hoyo (Disease Markers, 2012)
The Mannose 6 Phosphate/Insulin-like Growth Factor Receptor-2 (IGF2R) encodes a type-1 membrane protein that modulates availability of the potent mitogen, IGF2. We evaluated the associations between IGF2R non-synonymous genetic variants (c.5002G>A, Gly1619Arg(rs629849), and c.901C>G, Leu252Val(rs8191754)), circulating IGF2 levels, and colon cancer (CC) risk among African American and White participants enrolled in the North Carolina Colon Cancer Study (NCCCS). Generalized linear models were used to compare circulating levels of IGF2 among 298 African American and 518 White controls. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association of IGF2R genetic variants and CC risk. Women homozygous for the IGF2R c.5002 G>A allele, had higher mean levels of circulating IGF2, 828 (SD=321) ng/ml compared to non-carriers, 595 (SD=217) ng/ml (p-value=0.01). This pattern was not apparent in individuals homozygous for the IGF2R c.901 C>G variant. Whites homozygous for the IGF2R c.901 C>G variant trended towards a higher risk of CC, OR=2.2 [95% CI(0.9–5.4)], whereas carrying the IGF2R c.5002 G>A variant was not associated with CC risk. Our findings support the hypothesis that being homozygous for the IGF2R c.5002 G>A modulates IGF2 circulating levels in a sex-specific manner, and while carrying the IGF2R c.901 C>G may increase cancer risk, the mechanism may not involve modulation of circulating IGF2.